Terapi Asam Tranexamat dalam Bidang Dermatologi - Murlistyarini, Sinta; Pratama, Lucky (RSUD Dr. Saiful Anwar Province of East Java, 2022)
Tranexamic Acid, a synthetic lysine-analogue antifibrinolytic, was first patented in 1957. In the beginning, It is indicated for use in certain conditions with abnormal bleeding or bleeding tendencies in which local or systemic hyperfibrinolysis is considered to be involved. Recently its use has been increasing in the field of dermatology especially for use in chronic urticaria and angioedema, as well as melasma. Tranexamic acid is an inhibitor of plasmin, and it is a synthetic derivative of the amino acid lysine that reversibly blocks binding sites on the plasminogen molecule, inhibiting the plasminogen activator from converting plasminogen to plasmin thereby preventing degradation of the fibrin clot. Tranexamic acid can also reduce the release of plasmin-mediated vasoactive peptides such as bradykinin and histamine so that it can help control the symptoms of urticaria and angioedema. Tranexamic acid has an important role in melasma by reducing plasmin activation in UV-exposed skin, thereby inhibiting the release of arachidonic acid and prostaglandin E2, which in turn will inhibit the melanogenesis process. Tranexamic acid has been tried topically, orally, and intradermally in the treatment of dermatological disorder with minimal adverse effects. However, more randomized trials are needed to fully elucidate the exact mechanism of action, ideal route, frequency, and duration of administration of the drug, along with its potential to treat dermatological disorders.